Feline bartonellosis associated with some clinicopathological conditions in a veterinary hospital in Selangor, Malaysia - Bee Lee Ong; Hassan, U.L; Dhaliwal, G.K.; Watanabe, M; Yakubu, Y.; Tay, S.T (2017)
A cross-sectional study was conducted to determine the prevalence of feline bartonellosis and the associated clinicopathological findings in cats presented to the University Veterinary Hospital, Selangor, Malaysia from 2013–2014. Out of 284 cats examined, Bartonella DNA was detected in 48 (16.9%) cats using a specific polymerase chain reaction (PCR) assay targeting the internal transcribed spacer of Bartonella species. Bartonella henselae strain Houston was identified through BLAST analyses of randomly selected amplicons. Univariable analysis showed significant association of feline bartonellosis with cats < 2 years of age (OR 1.37, 95% CI 0.982–1.927, p = 0.036) and those presenting with ocular discharge (OR 3.211, 95% CI 1.422–7.248, p = 0.003). Significant associations of neutrophilia (OR 2.244, 95% CI 1.131–4.452, p = 0.019) and monocytosis (OR 2.476, 95% CI 1.154–5.312, p = 0.017) with bartonella infection in cats were observed. This study reports for the first time the prevalence (approximately 17%) of feline bartonellosis in Malaysia and highlights several clinicopathological factors associated with the disease.